2022
DOI: 10.1038/s41467-022-31998-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neuroendocrine plasticity by the RNA-binding protein ZFP36L1

Abstract: Some small cell lung cancers (SCLCs) are highly sensitive to inhibitors of the histone demethylase LSD1. LSD1 inhibitors are thought to induce their anti-proliferative effects by blocking neuroendocrine differentiation, but the mechanisms by which LSD1 controls the SCLC neuroendocrine phenotype are not well understood. To identify genes required for LSD1 inhibitor sensitivity in SCLC, we performed a positive selection genome-wide CRISPR/Cas9 loss of function screen and found that ZFP36L1, an mRNA-binding prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Finally, recent evidence is emerging that SCLC subtypes could be regulated by distinct epigenetic modifiers. Our data suggest that only the POU2F3 subtype is highly dependent on mSWI/SNF; in parallel, previous studies found that some SCLC cell lines of the ASCL1 subtype are highly dependent on the histone demethylase LSD1, where LSD1 is dispensable in other SCLC subtypes including in POU2F3-positive SCLC 49,50 . As such, the identification of the biochemical and chromatin regulatory interplay between lineage-specific TFs and each distinct chromatin regulatory entity is likely to yield improved understanding regarding SCLC pathogenesis and uncover additional therapeutic vulnerabilities associated with each SCLC subtype.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, recent evidence is emerging that SCLC subtypes could be regulated by distinct epigenetic modifiers. Our data suggest that only the POU2F3 subtype is highly dependent on mSWI/SNF; in parallel, previous studies found that some SCLC cell lines of the ASCL1 subtype are highly dependent on the histone demethylase LSD1, where LSD1 is dispensable in other SCLC subtypes including in POU2F3-positive SCLC 49,50 . As such, the identification of the biochemical and chromatin regulatory interplay between lineage-specific TFs and each distinct chromatin regulatory entity is likely to yield improved understanding regarding SCLC pathogenesis and uncover additional therapeutic vulnerabilities associated with each SCLC subtype.…”
Section: Discussionsupporting
confidence: 87%
“…We then focused on previously published NE-associated gene signatures. We observed a significant downregulation of NE-associated gene signatures based on the Chen (28) ( Figure 4E, S6B ) and Beltran (8) datasets ( Figure 4F, S6C). This trend was consistently mirrored in other NE-associated gene signatures ( Figure 4F ), leading us to investigate canonical neuronal transcription factors as a mechanism for the downregulation of the NE transcriptional program.…”
Section: Resultsmentioning
confidence: 92%
“…3c). Conversely, eIF6 knockdown markedly increased the neuroendocrine gene signature 42,43 (Fig. 3b and Supplementary Table 3), encompassing HES6, TOP2A, DLL3, NEUROD1, ASCL1, INSM1 and CHGA (Fig.…”
Section: Intervention Of Eif6 Sensitizes Sclc To Chemotherapymentioning
confidence: 98%
“…Gene set enrichment analysis of cytoplasmic RNA-seq was implemented by using GSEA software version 4.1.0. GSEA was performed using Hallmark EMT, 'Top 100 neuroendocrine genes' (Supplementary Table 3) 43 and KEGG in Fig. 3a,b,k respectively.…”
Section: Transcriptome and Translatome Analysismentioning
confidence: 99%